Mediation in the new dispute resolution landscape: A case for the enhancement of its application in Malaysia / Nurah Sabahiah Binti Mohamed - Nurah Sabahiah, Mohamed (2013)
This dissertation supports the paradigm shift in the administration of the civil justice system that strives for disputes to be resolved without adjudication. Various measures have been introduced and adopted in many jurisdictions across the common law world to achieve this overriding objective. It cannot be denied that alternative dispute resolution processes play an important and fundamental part in furthering and attaining this principal goal of the new procedural philosophy. The focal point of this dissertation in on the ‘mediation’ as an option for resolving disputes. Mediation, as a form of dispute resolution mechanism, is widely used to facilitate settlement of disagreements across many industries and nature of disputes. The mediation movement continues to gain momentum and popularity in more and more jurisdictions. The civil courts in these jurisdictions are beginning to utilize this mechanism to address and help overcome the tensions or recurrent challenges such as delay, costs and the backlog of cases in the civil justice system. The central theme of this dissertation is the role of mediation in speeding up the disposal of cases, relieving backlog of cases in the civil courts and giving convenient disposals for the disputing parties. Mediation should be regarded and adopted as an imperative component of the dispute resolution landscape in Malaysia. The greater use of private mediation will reduce the volume of cases filed into the civil court and the structured approach of court annexed mediation will speed up the disposal of cases and reducing the number of backlog cases. Therefore the dissertation proposes mediation to be enhanced at these two levels; the private mediation or non court mediation and at the stage of court annexed mediation. This dissertation takes the position that the civil justice system in Malaysia should encourage, facilitate and even mandate the use of mediation in the dispute resolution process. While mediation may not be the sole means to alleviate the problems relating to the delay and backlog of cases, it is submitted that mediation plays a pivotal role in combating the issues encountered by the civil justice systems in most jurisdictions. In this regard, this dissertation will analyse, the suitability of mediation in Malaysia, the problem of backlog cases in the civil court, the manner in which mediation is most effective and attractive for Malaysians and the effective application of private mediation and court annexed mediation in Malaysia. This dissertation will also scrutinize the use of mediation in other jurisdictions, particularly Singapore and Australia as the means to resolve disputes and to reduce backlog cases. We will draw from the experiences and lessons learnt from these jurisdictions; and offer suggestions for the adoption and/or reform of the mediation practice in Malaysia.